PENGARUH PEMANFAATAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG PADA KONDISI KEKURANGAN AIR - Ricky Indri Hapsari (BUANA SAINS, 2006)
Problems faced by dryland maize include less available water, erosion, soil structure-degradation, low organic matter content and other chemical elements. This experiment was carried out to elucidate the effect of manure application on the growth and yield of maize under water limited condition. The research was conducted in a glasshouse of Tribhuwana Tunggadewi University, Malang having altitude of 505 m above of sea level and the predominance soil type is an Andisol. The experiment used Randomized Block Design Factorial with two factors and three replicates. The first factor was manure application, consisting of: control (PO), chicken manure 15 t/ha (PI) and cow manure 15 t/ha (P2) treatments. The second factor was water volume consisting of: 150 mm/season (Al), 300 mm/season (A2) and 450 mm/season (A3) treatments. The results showed that there was a strong interaction between manure application and water volume in affecting grain dry weight per plant and plant total dry weight on harvest. Application of 15 t/ha chicken manure combined with 300 mm water volume/season gave the best yield compared to cow manure and control that each combined with 300 mm season water volume treatment